Role of Distributed Optical Fiber Sensors for FPGA Based implementation of pulse coding technique –An overview - Mulualem, Yelkal; Sirajudeen, M.Mohamed (IJRDO -Journal of Computer Science Engineering, 2015)
Over the last few years fiber sensing technology has been rapidly progressing for a wide range of industrial applications in strategic sectors such as energy, transportation and security, also including civil and structural engineering, geothermal and environmental monitoring. Advanced control electronics play a key role in such developments, allowing for significant performance improvement in the sensor systems. In this research paper to discuss the role of distributed optical fiber sensors in the implementation of FBGA based implementation of pulse coding technique. The proposed technique allows for a significant signal to noise ratio enhancement and consequent sensing range extension, allowing for temperature measurement over several tens of kilometres with meter scale spatial resolution